Mergers, acquisitions, and corporate restructurings - Gaughan, Patrick A. (Hoboken, New Jersey : Wiley, 2015)
"Corporate restructurings are an indispensable tool in building a new generation of re-engineered companies with the power and resources to compete on a global playing field. Written from a practical and historical perspective, Mergers, Acquisitions, and Corporate Restructurings, Fourth Edition carefully analyzes the strategies and motives that inspire M&As, the laws and rules that govern the field, as well as the offensive and defensive techniques of hostile acquisitions"--
Includes bibliographical references and index.
Keywords: Consolidation and merger of corporations; Corporate reorganizations; BUSINESS & ECONOMICS / Accounting / Managerial